A Promising Effect of Pravastatin For Reducing Preeclamsia Incidence In High Risk Pregnant Women - Zata, Fariska; Nasir, Mohammad (UNUSA Press, 2019)
Preeclamsia is still a threat in obstetrics because it is the leading cause of maternal death (15-20% in developing countries). Globally, preeclampsia causes 70,000-80,000 pregnant women to die and 500,000 babies die annually1, with increased morbidity such as prematurity and fetal growth disturbance2. The exact cause of preeclampsia is still not clearly known (also called